Pacific basin interdependencies: A case for large-scale economic cooperation? - Wilfried Lütkenhorst (Intereconomics, 1983)
Japan's meteoric economic rise, the hardly less impressive growth of a number of newly industrialised countries in South-East Asia and the enormous mineral wealth of the region have long caused academic and political observers to show keen interest in the economies of the Pacific. Proposals for institutionalised economic cooperation in this region have been under discussion since the mid sixties but have increased in number and significance in recent years; this paper analyses their objectives, limitations and chances.
Keywords: 330; Pacific Cooperation